Why volunteer? Evidence on the role of altruism, reputation, and incentives - Jeffrey P. Carpenter; Caitlin Knowles Myers (Institute for the Study of Labor (IZA), 2007)
Volunteering plays a prominent role in the charitable provision of goods and services, yet we know relatively little about why people engage in such prosocial acts. The list of possible motivations is long, but recent research has focused on altruism, reputational concerns, and material incentives. We present an analysis of a unique data set that combines an experimental measure of altruism, surveyed measures of other factors including reputational concerns, and call records from volunteer firefighters that provide an objective measure of the hours volunteered. Controlling for a variety of other explanations, we find that altruism and reputational concerns are positively associated with the decision to volunteer. Moreover, by utilizing variation in the presence and level of small stipends paid to the firefighters, we find that the positive effect of monetary incentives declines with reputational concerns, supporting a prediction that extrinsic incentives can crowd out prosocial behavior.
Keywords: 330; Volunteer; altruism; reputation; firefighter; Ehrenamtliche Arbeit; Altruismus; Prestige; Ökonomischer Anreiz; Crowding out; Brandschutz; USA